2022
DOI: 10.1096/fj.202101910rr
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid regulates pyruvate dehydrogenase kinase 4 (Pdk4) to modulate fuel utilization in the adult heart: Insights from wild‐type and β‐carotene 9′,10′ oxygenase knockout mice

Abstract: Regulation of the pyruvate dehydrogenase (PDH) complex by the pyruvate dehydrogenase kinase PDK4 enables the heart to respond to fluctuations in energy demands and substrate availability. Retinoic acid, the transcriptionally active form of vitamin A, is known to be involved in the regulation of cardiac function and growth during embryogenesis as well as under pathological conditions. Whether retinoic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…HSDL2 was found to be associated with fatty acid metabolism in the present study, and indeed the silencing of HSDL2 results in the inhibition of lipid metabolism, and therefore lower availability of the principal source of energy for cardiomyocytes, the oxidation of long-chain fatty acids (36), which causes heart failure. Low BCO2 expression causes cardiac retinoic acid deficiency and impaired metabolic flexibility in mice, and this is associated with impaired activation of the PDK4/PDH pathway (37). In addition, in vitro studies have shown that BCO2 activity is 7% higher in medium containing 5 mM Cu 2+ (38), suggesting that copper ions may be involved in various pathophysiological processes in cardiomyocytes through an effect on BCO2 activity, and thereby the PDK4/PDH pathway, which affects myocardial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…HSDL2 was found to be associated with fatty acid metabolism in the present study, and indeed the silencing of HSDL2 results in the inhibition of lipid metabolism, and therefore lower availability of the principal source of energy for cardiomyocytes, the oxidation of long-chain fatty acids (36), which causes heart failure. Low BCO2 expression causes cardiac retinoic acid deficiency and impaired metabolic flexibility in mice, and this is associated with impaired activation of the PDK4/PDH pathway (37). In addition, in vitro studies have shown that BCO2 activity is 7% higher in medium containing 5 mM Cu 2+ (38), suggesting that copper ions may be involved in various pathophysiological processes in cardiomyocytes through an effect on BCO2 activity, and thereby the PDK4/PDH pathway, which affects myocardial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, retinoids, such as fenretinide and tretinoin, have less evidence in the context of AF. However, it has been shown that these molecules can improve myocardial energy metabolism through modulation of pyruvate dehydrogenase kinase, decreasing the incidence of ventricular arrhythmias in murine models of ischemia-reperfusion [92][93][94]. The variety of compounds identified and their multiple mechanisms of action highlight the complexity of the mechanisms related to the development and perpetuation of this arrhythmia.…”
Section: Discussionmentioning
confidence: 99%